An unwinnable war : Australia in Afghanistan - Middleton, Karen Margaret (Melbourne University Publishing, 2011)
A decade on from the 2001 terrorist attacks on the United States, Australians are embroiled in one of the nation's longest military conflict#x97;the war in Afghanistan.An Unwinnable War charts the motives, ambitions and negotiations that carried Australia into Afghanistan: from the then Prime Minister John Howard's presence in Washington DC on September 11, 2001 to the #x91;transition#x92; plan to hand security to Afghan forces - all played out in the wake of increasing casualties. Based on interviews with key political and military figures in Australia and abroad, An Unwinnable War lays bare the.